Acne Comorbidities - Wang Y; Zhu M; Wu S; Zheng H (Dove Medical Press, 2022)
Yun Wang, Mingfang Zhu, Shuhui Wu, Huie Zheng Department of Dermatology, The Second Affiliated Hospital of Hunan University of Chinese Medicine, Changsha, People's Republic of ChinaCorrespondence: Mingfang Zhu, Department of Dermatology, The Second Affiliated Hospital of Hunan University of Chinese Medicine, 233 Cai E North Road, Kaifu District, Changsha, People's Republic of China, Tel +86-13907317358, Fax +86-731-84917727, Email cszmf@162.comAbstract: Acne vulgaris is a multifactorial chronic inflammatory disorder of the pilosebaceous unit, and it represents the most common skin disease affecting about 85% of adolescents in Western populations. The prevalence of acne vulgaris in developed countries is higher than that in developing countries.Emerging data has shown some systemic diseases closely associated with acne, including obesity, diabetes mellitus, cardiovascular diseases, metabolic syndrome (Mets), and so on.This review summarizes acne-associated diseases that have been reported in studies, and analyzes the possible co-pathogenesis of these diseases and acne.Keywords: acne, comorbidity, metabolic diseases, diabetes mellitus, obesity